Properties of Economic Income in a Private Information Setting* - FARLEE, MITCHELL A.; FELLINGHAM, JOHN C.; YOUNG, RICHARD A. (Contemporary Accounting Research, 1996)
Abstract. This paper adopts a valuation perspective within an asymmetric information setting and explores properties of economic income. The optimal intertemporal contract induces an accrual component of income which would not exist absent the information problem. The contracting solution introduces a dampening effect—if cash flow increases by one dollar, income increases by less than one dollar. Thus, the accrual is inversely related to cash flows. Further, this dampening is greater for more favorable cash outcomes. Résumé. Les auteurs adoptent la perspective de l'évaluation en situation d'asymétrie de l'information et explorent les propriétés du bénéfice économique. Le contrat intertemporel optimal fait intervenir une amplification du bénéfice qui n'existerait pas si ce n'était de la présence du problème d'information. La solution contractuelle amène un effet atténuateur — c'est‐à‐dire qu'à une augmentation du flux monétaire de un dollar correspond une augmentation du bénéfice de moins de un dollar. Ainsi, l'amplification est en relation inverse avec les flux monétaires. En outre, l'atténuation est plus marquée dans le cas de résultats monétaires plus avantageux.